Bridging book: a not-so-electronic children's picturebook - Figueiredo, Ana Carina (2013)
We present and technically describe the implementation of a book prototype: the Bridging Book, a children's mixed-media picturebook that blurs the line between printed and electronic books. Bridging book consists of a printed book and a digital device, placed side-by-side, with synchronized content. Thumbing through the book's pages triggers the device to display the complementary digital content. The physical book requires no batteries or wires. In the current version, the printed illustrations on each page of the physical book are extended into the device screen, offering further interaction. The content can be explored both linearly by reading and thumbing the printed book and/or exploring the interaction on the digital device. We also briefly explain the planned future study observation, with children, to evaluate our prototype.